Seaweed mariculture: an economically viable alternate livelihood option (ALO) for fishers - Narayanakumar, R. (Indian Journal of Fisheries, 2011)
Seaweed mariculture offers an economically sustainable livelihood option for fisherwomen, who, with little effort can contribute significantly to the household income. Ealier in India, seaweeds were collected from natural stocks only. Later due to the indiscriminate collection from the natural stock and consistent demand from industries for high quality seaweeds, research on seaweed farming was initiated by Central Salt and Marine Chemicals Research Institute (CSMCRI) and Central Marine Fisheries Research Institute (CMFRI) in the 1960’s. Today, seaweed farming techniques have been standardised, improved and made economically viable. The present paper makes an attempt to evaluate the economic performance of seaweed farming, including the employment generated in Ramanathapuram District of Tamil Nadu. The average annual net income for the three-year farming period (Rs. 6.76 lakh) was higher than the initial investment (Rs. 5.97 lakh), indicating a payback period of lesser than a year. The estimated net present value (at 20% discount rate) was Rs. 1.30 million (implying an IRR, >100%) while the benefit-cost ratio was 1.70. All these indicators substantially establish the economic and financial feasibility of seaweed farming in Tamil Nadu. The employment potential of seaweed farming at Ramanathapuram District has been estimated at 7,65,000 man days with current development projections benefiting 5,000 families in the near future.